2014
DOI: 10.1021/ac501088q
|View full text |Cite
|
Sign up to set email alerts
|

Screening of DNA Aptamers against Myoglobin Using a Positive and Negative Selection Units Integrated Microfluidic Chip and Its Biosensing Application

Abstract: An aptamer screening method using a positive and negative selection units integrated microfluidic chip was introduced. Here, myoglobin (Myo), one of the early markers to increase after acute myocardial infarction, was used as the model. After 7-round selection, the aptamers, which exhibited dissociation constants (K(d)) in the nanomolar range (from 4.93 to 6.38 nM), were successfully obtained using a positive and negative selection units integrated microfluidic chip. The aptamer with the highest affinity (K(d)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 43 publications
0
49
0
Order By: Relevance
“…Hemin and ABTS were purchased from Sigma-Aldrich (USA). DNA1 probe (5 -CCC TCC TTT CCT TCG ACG TAG ATC TGC TGC GTT GTT CCG ATT TTT AGA TGG CTA TGC AA-3 ) [27] and DNA2 probe (5 -T 17 GGG TAG GGC GGG TTG GGT 10 TTG CAT AGC CAT CT-3 ) were synthesized by Sangon Biotech. (Shanghai) Co., Ltd.…”
Section: Materials and Reagentsmentioning
confidence: 99%
“…Hemin and ABTS were purchased from Sigma-Aldrich (USA). DNA1 probe (5 -CCC TCC TTT CCT TCG ACG TAG ATC TGC TGC GTT GTT CCG ATT TTT AGA TGG CTA TGC AA-3 ) [27] and DNA2 probe (5 -T 17 GGG TAG GGC GGG TTG GGT 10 TTG CAT AGC CAT CT-3 ) were synthesized by Sangon Biotech. (Shanghai) Co., Ltd.…”
Section: Materials and Reagentsmentioning
confidence: 99%
“…All oligonucleotides used in this study were synthesized according to Yang's group 35 by Sangon Biotech Co. Ltd. (Shanghai, China). Each single-stranded DNA (ssDNA) library member consisted of 40 nucleotide (nt) randomized sequences and 20 nt primer sites (5 0 -TAMRA-GACAGGCAGGACACCGTAAC-N40-CTGCTACCTCCCTCCTCTTC-3 0 ).…”
Section: Dna and Library Preparationmentioning
confidence: 99%
“…A more conventional chromatographic device was recently demonstrated that uses pairs of on-chip microcolumns which overcome these sampling limitations and allow for multiplexing and simultaneous negative selections. 124 …”
Section: Filtering Targets: Magnetic Beadsmentioning
confidence: 99%